Cardiac Structure–Function MRI in Patients After Heart Transplantation. Issue 3 (24th August 2018) - Dolan, Ryan S.; Rahsepar, Amir A.; Blaisdell, Julie; Lin, Kai; Suwa, Kenichiro; Ghafourian, Kambiz; Wilcox, Jane E.; Khan, Sadiya S.; Vorovich, Esther E.; Rich, Jonathan D.; Anderson, Allen S.; Yancy, Clyde W.; et al.
Abstract : Background: Following heart transplantation (Tx), recipients are closely monitored using endomyocardial biopsy, which is limited by cost and invasiveness, and echocardiography, which is limited regarding detailed structural and functional evaluation. Purpose: To test the feasibility of comprehensive structure–function cardiac MRI as a noninvasive modality to assess changes in myocardial structure and function. Study Type: Prospective. Subjects: MR was performed in 61 heart transplant recipients (age 47.9 ± 16.3 years, 39% female) and 14 age‐matched healthy controls (age 47.7 ± 16.7 years, 36% female). Field Strength/Sequence: 1.5T; 2D CINE steady state free precession (SSF)P imaging, T2 ‐mapping, pre‐ and postgadolinium contrast T1 ‐mapping, and tissue‐phase mapping (TPM). Assessment: Quantification of myocardial T2 (as a measure of edema), pre‐ and post‐Gd T1 (allowing calculation of extracellular volume (ECV) to estimate interstitial expansion), and TPM‐based assessment of peak regional left ventricular (LV) velocities, dyssynchrony, and twist. Statistical Tests: Comparisons between transplant recipients and controls were performed using independent samples t ‐tests. Relationships between structural (T2, T1, ECV) and functional measures (myocardial velocities, dyssynchrony, twist) were assessed using Pearson correlation analysis. Results: T2 and T1 were significantly elevated in transplant recipients compared to controls (global T2 : 50.5 ± 3.4 msec vs. 45.2 ± 2.3 msec, P < 0.01; global T1 : 1037.8 ± 48.0 msec vs. 993.8 ± 34.1 msec, P < 0.01). Systolic longitudinal function was impaired in transplant recipients compared to controls (reduced peak systolic longitudinal velocities, 2.9 ± 1.1 cm/s vs. 5.1 ± 1.2 cm/s, P < 0.01; elevated systolic longitudinal dyssynchrony, 60.2 ± 30.2 msec vs. 32.1 ± 25.1 msec, P < 0.01). Correlation analysis revealed a significant positive relationship between T2 and ECV ( r = 0.45, P < 0.01). In addition, peak systolic longitudinal velocities demonstrated a significant inverse relationship with T2 (global r = –0.29, P = 0.02), and systolic radial dyssynchrony was positively associated with peak T2 and peak T1 ( r = 0.26, P = 0.04; r = 0.27, P = 0.03). Data Conclusion: MR techniques are sensitive to structural and functional differences in transplant recipients compared to controls. Structural (T2, T1 ) and functional (peak myocardial velocities, dyssynchrony) measures were significantly associated, suggesting a structure–function relationship of cardiac abnormalities following heart transplant. Level of Evidence : 2 Technical Efficacy Stage : 2 J. Magn. Reson. Imaging 2019;49:678–687.